Metabolic abnormalities and genitourinary tract anatomical alternations in patients with recurrent urolithiasis - John Neil; Jose Binu (Archives of Clinical and Experimental Surgery, 2017)
Background: Preventing the recurrence of episodes of stone formation is the focus of interest for patients. This retrospective study aimed to determine the prevalence of metabolic abnormalities and anatomical alterations of the genitourinary tract in patients with recurrent urolithiasis. Methods: Patients who had recurrent renal calculi were included. Laboratory assessment was performed on two 24-hour samples of urine. The first 24-hour urine was a random specimen and the second was obtained after the patient had been on a sodium-, oxalate- and calcium-restricted diet for at least one week. The patients with hypercalciuria further underwent fasting and calcium load testing and were assessed in terms of parathyroid hormone levels. Urine culturing was conducted to rule out urinary tract infection. All patients were evaluated with ultrasound and intravenous pyelography for any anatomical abnormalities. Results: A total of 30 patients (20 male and 10 females) were included in the study. The most frequently found metabolic alterations were hypercalciuria, low urinary volume, urinary tract infection and hyperoxaluria. Anatomic alterations were found in 26.5% of patients, mainly in the form of renal cysts, pelvi-ureteric junction obstructions, horse shoe kidneys and atrophic kidney. Conclusions: 80% of patients with recurrent stone disease had some measure of metabolic abnormality to account for the disease. The use of two 24-hour urine samples significantly improved the detection rate of metabolic abnormalities compared to a single sample. The major limitation of this study was the small number of patients as well as the short study duration. [Arch Clin Exp Surg 2017; 6(2.000): 81-85]